PERBEDAAN HASIL BELAJAR DAN AKTIVITAS SISWA MENGGUNAKAN MODEL PEMBELAJARAN TIPE JIGSAW DAN TIPE ROLE PLAYING PADA MATERI SISTEM PEREDARAN DARAH MANUSIA KELAS XI IPA SMAN 3 PEMATANGSIANTAR - Desy Putri Sari; Ely Djulia (Jurnal Pelita Pendidikan, 2018)
This study aims to determine the differences of student learning outcomes and student learning activities using Jigsaw learning model and Role Playing learning model on Human Circulatory Systems in SMA 3 Pematangsiantar.This type of research is quasi-experimental with two group pre-test and post-test design. The population is all students of class XI IPA SMA Negeri 3 Pematangsiantar consisting of 7 classes. Sampling is done by purposive sampling, the sample is taken from the population as much as two classes because of the class is heterogeneous (superior) and the selection of samples based on the instructions of the tutors and the school. The instrument used for the test result of learning as much as 25 questions and student activity observation sheet. Class XI IPA 3 is given treatment with Role Playing learning model. Class XI IPA 5 is given treatment with Jigsaw learning model. From the calculation result of t-test two parties obtained tcount = 3.30 and ttable = 1.99, so tcount> ttable. Data acquisition shows that there is a significant difference between Jigsaw and Role Playing type of learning model on learning outcomes and student learning activities on Human Circulatory System material in class XI IPA SMA Negeri 3 Pematangsiantar. Where classes taught by the Jigsaw learning model get higher learning outcomes than the classes taught by the Role Playing learning model. Student activity on Jigsaw type and Role Playing learning can be categorized quite actively.Keywords: Jigsaw, Role Playing, learning outcomes, student learning activities.